Prince Sambernyawa’s Mnemonic Dish as the Inspiration for Creating Batik Motifs in Couture Fashion - Daniel Oktafianus; Syarifah Nur Hajja (Information Technology and Science (ITScience), 2026)
This final project is titled “Raden Mas Said’s Mnemonic Dish as the Concept Behind the Creation of Batik Motifs for Couture Apparel.” The creation of this work is inspired by Raden Mas Said’s struggle and by the philosophy of jenang katul, which serves as a symbol of his closeness to the common people. The mnemonic concept was used as the basis for this creation because mnemonics are techniques that help people remember through specific symbols and experiences. Jenang katul was chosen as a mnemonic tool because it holds historical and philosophical significance and is used as an offering in Javanese traditions. The creation of the batik motifs was inspired by the story of Raden Mas Said, who drew a war strategy from Nyi Ageng Karang’s simple advice on how to eat jenang katul. This story is represented through the “Nuju Pusat” motif, which depicts a strategy of attacking from the periphery toward the center. Furthermore, this work also highlights the values of the Tri Dharma and Raden Mas Said’s spirit of nationalism, such as a sense of belonging to the homeland, the courage to defend one’s birthplace, and a spirit of unity. Through this couture fashion piece based on batik motifs, it is hoped that the public will view the work as a reminder to love, preserve, and develop Indonesia’s culture and homeland.